Perspectives of HPV vaccine decision-making among young adults: A qualitative systematic review and evidence synthesis - Namoonga M. Mantina; Jonathan Smith; Flavia Nakayima Miiro; Priscilla Anne Magrath; Deborah Jean McClelland; Leila Barraza; John Ruiz; Purnima Madhivanan (PLoS ONE, 2025)
Background Despite the demonstrated safety and effectiveness of HPV vaccines in preventing HPV-related cancers, global vaccine coverage remains low. The suboptimal adolescent HPV vaccine coverage rate leaves many young adults at increased risk for developing vaccine preventable HPV-related cancers. This qualitative evidence synthesis (QES) aims to examine the HPV vaccination perspectives of young adults globally and identify the barriers and facilitators to HPV vaccine uptake and decision-making processes. Methods A comprehensive search was conducted on October 2023 across seven databases to identify studies that reported on HPV vaccination among young adults aged 18–26 years and used qualitive study methods or analysis techniques. Results Forty-two studies were purposively sampled for inclusion, presenting 29 findings across 10 thematic categories. Vaccine eligible young adults believed that they had aged out of eligibility for HPV vaccination. There was also a perspective that condom use, and regular screenings were alternatives to vaccination in preventing HPV infections. Challenges included scheduling appointments, requirements for multiple shots, and vaccine cost. There was also concern for the gendered nature of vaccine promotion. Lastly, despite being at the age to make autonomous decisions, parents were still influential and active in the vaccine decision-making process for their children. Conclusion The novelty of this study, as one of the principal QES on catch-up HPV vaccination, presents findings that underscore the complexity of factors across multiple ecological levels which may aid or impede vaccination uptake among young adults and provide important considerations for interventions, programs, and policies aimed at addressing HPV vaccination disparities among young adults.